Betwixt and Between: Trauma, Survival and the Aboriginal Troopers of the Queensland Native Mounted Police. Issue 3 (2nd July 2020) - Burke, Heather; Barker, Bryce; Wallis, Lynley; Craig, Sarah; Combo, Michelle
ABSTRACT: Much has been written about the history of the Queensland Native Mounted Police, mostly focussing on its development, its white officers, how much the Colonial Government genuinely knew about the actions of the Force, and how many people were killed during the frontier wars. Far less attention has been given to the Aboriginal men of the force, the nature of their recruitment, and the long-term traumatic impacts on Aboriginal peoples' and communities' psyches rather than broadscale changes to Aboriginal culture per se. This article examines the historical and ongoing psychological impacts of dispossession and frontier violence on Aboriginal people. Specifically, we argue that massacres, frontier violence, displacement, and the ultimate dispossession of land and destruction of traditional cultural practices resulted in both individual and collective inter-generational trauma for Aboriginal peoples. We posit that, despite the Australian frontier wars taking place over a century ago, their impacts continue to reverberate today in a range of different ways, many of which are as yet only partially understood.